Peran Gaya Kepemimpinan, Kompetensi Dan Lingkungan Kerja Terhadap Kinerja Guru Pada Sekolah Dasar Islam Terpadu “QR” Kota Pekanbaru - Sri Dewi, Diana (Eko dan Bisnis: Riau Economic and Business Review, 2024)
This study aims to analyze (1) The influence of leadership style partially on the performance of teachers at integrated islamic elementary school ““QR”” in Pekanbaru City(2) The effect of partial competence on the performance of teachers at integrated islamic elementary school ““QR”” in Pekanbaru City (3) The influence of the work environment partially on the performance teachers at integrated islamic elementary school ““QR”” in Pekanbaru City (4) The influence of leadership style, competence, and work environment simultaneously on the performance of teachers at integrated islamic elementary school ““QR”” in Pekanbaru City (5).. The sample selection in this study was carried out using a stratified random sample method (stratified sampling) with sampling using the saturated method, with a sample of 31 teachers at integrated islamic elementary school  in Pekanbaru City. Data analysis used Multiple Regression Analysis. The results showed that (1) Partially leadership style had a significant effect on the performance of teachers at integrated islamic elementary school ““QR”” in Pekanbaru City with a value of 2,408 Tvalue > 2,0158 Ttable (2) Partially competence does not have  significant effect on the performance of teachers at integrated islamic elementary school ““QR”” in Pekanbaru City with a value of -2,078 Tvalue < 2,0158 Ttable (3) Partially the work environment dose not have significant effect on the performance of teachers at integrated islamic elementary school ““QR”” in Pekanbaru City with a value of -0,553 Tvalue < 2,0158 Ttable  (4) Simultaneously leadership style, competence, and work environment have a significant effect on the performance of teachers at integrated islamic elementary school ““QR”” in Pekanbaru City with a value of 3,688 Fvalue > 2,960 (Ftable).